Suppression of Aluminum Corrosion in Lithium Bis(trifluoromethanesulfonyl)imidebased Electrolytes by the Addition of Fumed Silica - Hamenu Louis; 이영기; 김광만; 조원일; 고장면 (Bulletin of the Korean Chemical Society, 2013)
The corrosion property of aluminum by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt is investigated in liquid and gel electrolytes consisting of ethylene carbonate/propylene carbonate/ethylmethyl carbonate/diethyl carbonate (20:5:55:20, vol %) with vinylene carbonate (2 wt %) and fluoroethylene carbonate (5 wt %) using conductivity measurement, cyclic voltammetry, scanning electron microscopy, and energy dispersive X-ray spectroscopy. All corrosion behaviors are attenuated remarkably by using three gel electrolytes containing 3 wt % of hydrophilic and hydrophobic fumed silica. The addition of silica particles contributes to the increase in the ionic conductivity of the electrolyte, indicating temporarily formed physical crosslinking among the silica particles to produce a gel state. Cyclic voltammetry also gives lower anodic current responses at higher potentials for repeating cycles, confirming further corrosion attenuation or electrochemical stability. In addition, the degree of corrosion attenuation can be affected mainly by the electrolytic constituents, not by the hydrophilicity or hydrophobicity of silica particles. KCI Citation Count: 18